Distributed environment for Web-based network management - Spolidoro, F.; Rodriguez, N. (Proceedings LCN 2001. 26th Annual IEEE Conference on Local Computer Networks, 2001)
The use of scalable management tools is becoming more and more important for integrated management of different network platforms. This work explores the resources of the interpreted language Lua to create a flexible environment for Web-based distributed network management. This environment includes services for monitoring and asynchronous event handling, both available through CORBA interfaces. The dynamic characteristics of our environment allow the administrator to extend or modify functionality without stopping the system, and also to redefine dynamically the group of servers supporting the network management application.